Leadership for Student Participation in Data-Use Professional Learning Communities - Hilde Forfang; Cindy Louise Poortman; Mette Marit Jenssen; Kim Schildkamp (Education Sciences)
Student participation in educational decision making, for example, through data-informed decision making, can have a positive effect on student well-being, engagement, and performance. Teachers play a crucial role in student participation, and leadership is a main factor influencing teacher professional development, which can lead to improved experiences and outcomes for students. In this study, we aimed to combine the benefits associated with data-informed decision making with those associated with Professional Learning Communities. Moreover, we included students as PLC participants. This study therefore focuses on the question how school leaders can support teachers in connection with student participation in data-use PLCs. Based on previous research, we used leadership core functions needed for successful PLCs to describe school leaders’ roles in an approach to student participation that combines the pedagogical analysis model and Shier’s model for student participation. School leaders and teachers from five schools participating in the previous study were interviewed to describe school leaders’ roles. The findings show what concrete school leader activities can support teachers in connection with student participation in data-use PLCs and what implications this has for practice, policy, and further research.